Design of a curved， band-pass frequency selective surface radome with steep cut-off performance - Wang Yifu; Jiang Kun; He Lintao; Chen Xuan; Chen Yiqiao (Dianzi Jishu Yingyong)
The traditional frequency selective surface（FSS）radome has the problem such as high structural profile and insufficient out of band cut-off performance. A design method for low-profile and band-pass FSS radome with steep out of band cut-off in K-band is presented. By using multilayers non-resonant constituting elements and the electromagnetic strong coupling techniques, a third-order band-pass radome in K-band is realized. It is worth noting that it not only has an extremely low profile，but also achieves a rapid steep transition from pass to stop band. Further，the K-band curved FSS radome prototypes was fabricated by using multi-layer circuit board pressing technology and radome molding technology, and the fabricating accuracy of FSS pattern as well as the radome surface shape is effectively ensured. Finally，the transmission characteristics of the radome and its influence on the antenna pattern are tested and verified. The measurement results agree very well with the simulated results, and the feasibility of the design method is demonstrated.